Biodegradation of Poly(vinyl alcohol) using Pseudomonas alcaligenes - Bharathiraja, B.; Jayamuthunagai, J.; Jayakumar, M.; Arul Kirubakaran, M.; Vivek, P.; Chandran, M.; Praveen Kumar, R. (Asian Journal of Chemistry, 2013)
Biodegradation of polymeric material has gained considerable attention in recent years, mainly because of the environmental pollution caused by the waste polymers. Several studies have been carried out on the biodegradation of polymers using polymer degrading microorganisms. This work deals with the biodegradation of poly(vinyl alcohol) (PVA), a water soluble synthetic polymer prepared by the hydrolysis of polyvinyl acetate. Poly(vinyl alcohol) was subjected to biodegradation by the microorganism Pseudomonas alcaligenes. P. aclaligenes is a gram negative bacterium that can degrade polycyclic aromatic hydrocarbons. The degradation of PVA by P. alcaligenes was studied using batch method and flow method. The extent of degradation was studied by evaluating the effect of initial concentration of the PVA, effect of size of the inoculum, effect of pH and effect of flow rate. The studies revealed effective results of PVA degradation. In batch method the degradation rate was higher when the initial concentration of PVA was less and pH maintained under alkaline conditions. In flow method the degradation rate was greater at minimum flow rate was maintained in the upflow bioreactor. The degradation capabilities of Pseudomonas alcaligenes have been brought out using effective degradation techniques. The results of this research would help in minimizing the pollution caused by poly(vinyl alcohol) and poly(vinyl alcohol) based materials.